No difference in clinical parameters and drug retention in PsA patients receiving b/tsDMARD monotherapy versus combination with methotrexate: data from the RABBIT-SpA registry - Regierer, Anne Constanze; Kiefer, David; Schett, Georg; Krause, Andreas; Weiß, Anja; Sewerin, Philipp; Strangfeld, Anja (RMD Open, 2024)
Background The potential benefit of methotrexate (MTX) in combination with biologic (b) and targeted synthetic (ts) disease modifying anti-rheumatic drugs (DMARDs) in psoriatic arthritis (PsA) is still a matter of debate. Objectives To compare clinical and patient reported characteristics as well as drug retention rates in PsA patients receiving b/tsDMARD monotherapy or in combination with MTX. Methods RABBIT-SpA is a prospective longitudinal cohort study including axSpA and PsA patients. In this analysis, PsA patients were stratified into two groups: starting b/ tsDMARD as monotherapy or in combination with MTX. Treatment retention was compared by drug survival analysis. Results 69% of the patients (n=900) started b/tsDMARD as monotherapy while 31% were treated in combination with MTX (n=405). At baseline, clinical domains like skin, nail and joint affection, dactylitis, enthesitis and axial involvement were similar between the groups. Only the patients’ satisfaction concerning tolerability of the previous treatment was significantly better in the combination group at treatment start. Drug retention rates did not differ between the groups (p=0.4). At 6/12 months, 66%/48% of patients in monotherapy and 67%/48% in the combination group were still on their original treatment. Conclusions We did not identify any clinical parameters with notable influence on the choice of b/tsDMARD mono or MTX-combination therapy in PsA. Drug retention rates are similar between mono and combination therapy. It seems that the decision to continue MTX at initiation of b/ tsDMARDs is mostly based on the subjective tolerability of MTX treatment.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Biological Therapy; Epidemiology; Methotrexate; Psoriatic Arthritis